Engaging students with learning technologies - Herrington, Anthony; Schrape, Judy; Singh, Kuki (Curtin University, 2012)
Curtin University initiated its eScholar program in 2009 making funds available for academic staff to implement innovative teaching using Curtin’s extensive suite of learning technologies. The program is based on the philosophy of engaging students with learning technologies that support their growing understanding through authentic and assessable activities.This publication presents the research findings of each of the eScholar projects conducted in 2010 and 2011. Each chapter has undergone a process of double-blind review resulting in high quality descriptions of learning using current and emerging technologies. The publication is divided into 6 sections based on these technologies.University teaching and learning is faced with many challenges. A major one is recognising appropriate learning technologies and their use that support ways in which adults learn. Rapid advances in technologies can easily seduce those with limited understanding of adult learning. This publication offers clear directions founded on teacher and learner experiences grounded in real classroom activity.